Fen and sea : the landscapes of south-east Lincolnshire AD 500-1700 - Simmons, I. G. (Ian Gordon), 1937- (Windgather Press, 2022)
Reknown environmental archaeologist Ian Simmons synthesises detailed research into the landscape history of the coastal area of Lincolnshire between Boston and Skegness and its hinterland of Tofts, Low Grounds and Fen as far as the Wolds. With many excellent illustrations Simmons chronicles the ways in which this low coast, backed by a wet fen, has been managed to display a set of landscapes which have significant differences that contradict the common terminology of uniformity, calling the area 'flat' or everywhere from Cleethorpes to Kings Lynn as 'the fens'. 0These usually labelled 'flat' areas of East Lincolnshire between Mablethorpe and Boston are in fact a mosaic of subtly different landscapes. They have become that way largely due to the human influences derived from agriculture and industry. Between the beginning of Norman rule and the advent of pumped drainage, a number of significant changes took place. Foremost was the reclamation of land from the sea, which took place in both medieval times and the early modern decades. Part of the sequence along the coast of The Wash was due to land creation from the wastes of the salt industry. Next in importance was the management of the East Fen, both for its resources (mostly of a biological nature) and to keep it from flooding the surrounding lands and settlements. All these changes required a knowledge of water management that depended upon gravity until the coming of the drainage mill towards 1700.